THE METHODOLOGY OF HAMMAD B. SALAMAH IN HADITH PRESERVATION DURING THE ERA OF THE TABI‘ AL-TABI‘IN (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2025)
The methodology employed by Ḥammād ibn Salamah in preserving hadith during the tābiʿ al-tābiʿīn era emerged in response to a critical period marked by the proliferation of fabricated hadith, driven by intense political conflict and sectarian rivalry within the early Muslim community. This situation raised serious concerns about the integrity of Islamic teachings, particularly the authenticity of prophetic traditions. This study aims to examine and analyze the specific methodological strategies undertaken by Ḥammād ibn Salamah to ensure the preservation and authenticity of hadith during this volatile period. Utilizing a qualitative approach through literature-based research, the findings reveal that Ḥammād ibn Salamah applied a rigorous and systematic methodology in both receiving and transmitting hadith. His approach was characterized by strict scrutiny of narrators’ credibility, careful assessment of their memorization accuracy, and mastery in the auxiliary sciences of hadith such as rijāl al-ḥadīth, tadlīs al-ḥadīth, asmāʾ al-rijāl, sanad criticism, and textual analysis. These findings underscore the pivotal role of Ḥammād ibn Salamah in safeguarding the prophetic legacy against the infiltration of spurious and weak narrations. This research contributes to contemporary hadith scholarship by highlighting the methodological integrity of early Muslim scholars (salaf) and their enduring relevance in addressing issues of authenticity and transmission in hadith studies today.[Metodologi yang diterapkan oleh Ḥammād ibn Salamah dalam menjaga keotentikan hadis pada masa tābiʿ al-tābiʿīn muncul sebagai respons terhadap situasi kritis yang ditandai oleh maraknya pemalsuan hadis, yang dipicu oleh konflik politik dan pertentangan antar kelompok dalam komunitas Muslim awal. Kondisi ini menimbulkan kekhawatiran serius terhadap integritas ajaran Islam, khususnya dalam hal keaslian tradisi kenabian. Penelitian ini bertujuan untuk mengkaji dan menganalisis secara mendalam strategi metodologis yang ditempuh oleh Ḥammād ibn Salamah dalam memastikan pelestarian dan keotentikan hadis di tengah situasi yang penuh gejolak tersebut. Dengan menggunakan pendekatan kualitatif berbasis studi pustaka, temuan penelitian menunjukkan bahwa Ḥammād ibn Salamah menerapkan metode yang ketat dan sistematis dalam proses penerimaan dan periwayatan hadis. Pendekatannya ditandai dengan ketelitian tinggi dalam menilai kredibilitas perawi, pengujian kekuatan hafalan mereka, serta penguasaan dalam ilmu bantu hadis seperti rijāl al-ḥadīth, tadlīs al-ḥadīth, asmāʾ al-rijāl, kritik sanad, dan analisis matan hadis. Temuan ini menegaskan peran penting Ḥammād ibn Salamah dalam menjaga kemurnian warisan kenabian dari infiltrasi hadis palsu dan lemah. Penelitian ini diharapkan dapat memberikan kontribusi bagi pengembangan studi hadis kontemporer dengan menyoroti integritas metodologis para ulama salaf dan relevansinya dalam menjawab persoalan otentisitas dan transmisi hadis di era modern.]